Brasilomma gen. nov., a new prodidomid genus from Brazil (Araneae, Prodidomidae) - Brescovit, Antonio Domingos; Ferreira, Rodrigo Lopes; Silva, Marconi Souza; Rheims, Cristina Anne (Zootaxa, 2012)
The genus Brasilomma gen. nov. is described to include B. enigmatica sp. nov. collected in three caves from the state ofMinas Gerais, Brazil. This genus can be distinguished from the remaining South American Prodidomidae by the malepalps with large triangular projection, covering the base of the embolus, the distal border of the tegulum projected overthe base of the conductor and median apophysis and by the female epigynum with blind, posterior atrium and anteriorlywidened copulation ducts arising from an internal, mushroom-shaped plate. In addition, aspects of the species natural history are described.